Incorporating 2D γ-Al2O3 nanosheets into the flexible PEO-based solid electrolyte for lithium metal batteries. (1st January 2023) - Song, Jiechen; Xu, Yuxing; Zhou, Yuncheng; Wang, Pengfei; Feng, Hailan; Yang, Jun; Zhuge, Fuchang; Tan, Qiangqiang
Abstract: Solid polymer electrolytes using polyethylene oxide (PEO) are promising for boosting the safety of lithium metal batteries (LMBs), but suffer from low ionic conductivity due to high crystallinity and poor segment motion of PEO. Adding plasticizers like succinonitrile (SN) is one of the solutions to improve the ionic conductivity of PEO, but it sacrifices the cycle performances of LMBs. In addition, the ability to conduct lithium ions of PEO-SN matrixes is yet to be improved. Herein, two-dimensional γ-Al2 O3 nanosheets are first introduced into the PEO-SN matrix to facilitate the long-range migration of lithium ions and improve the electrochemical properties of PEO-SN matrix, realizing the new design of traditional materials. The mechanism between γ-Al2 O3 nanosheets and the polymer matrix is discussed. The addition of γ-Al2 O3 nanosheets improves the ionic conductivities and cycle performances of PEO-LiTFSI-SN (PLS) electrolytes. In specific, the ionic conductivity at 25 °C of the PEO-LiTFSI-SN-Al2 O3 nanosheet (PLS-A) electrolyte is up to 2.02 × 10 −4  S cm −1 . Meanwhile, the electrochemical properties of Li/PLS-A/LiFePO4 are tested, with a low overpotential change of 0.06 V, coulombic efficiency above 99.6%, and capacity retention of 95% at 0.5C and 60 °C after 50 cycles. The solid electrolyte system provides a feasible strategy for the application of 2D nanofillers in PEO polymer electrolytes.